Neutropenia exacerbates infection by Acinetobacter baumannii clinical isolates in a murine wound model - Grguric-Smith, Laryssa M.; Lee, Hiu H.; Gandhi, Jay A.; Brennan, Melissa B.; DeLeon-Rodriguez, Carlos M.; Coelho, Carolina; Han, George; Martinez, Luis R. (Frontiers in Microbiology, 2015)
The Gram negative coccobacillus Acinetobacter baumannii has become an increasingly prevalent cause of hospital-acquired infections in recent years. The majority of clinical A. baumannii isolates display high-level resistance to antimicrobials, which severely compromises our capacity to care for patients with A. baumannii disease. Neutrophils are of major importance in the host defense against microbial infections. However, the contribution of these cells of innate immunity in host resistance to cutaneous A. baumannii infection has not been directly investigated. Hence, we hypothesized that depletion of neutrophils increases severity of bacterial disease in an experimental A. baumannii murine wound model. In this study, the anti-Ly-6G monoclonal antibody (mAb), 1A8, was used to generate neutropenic mice and the pathogenesis of several A. baumannii clinical isolates on wounded cutaneous tissue was investigated. We demonstrated that neutrophil depletion enhances bacterial burden using colony forming unit determinations. Also, mAb 1A8 reduces global measurements of wound healing in A. baumannii-infected animals. Interestingly, histological analysis of cutaneous tissue excised from A. baumannii-infected animals treated with mAb 1A8 displays enhanced collagen deposition. Furthermore, neutropenia and A. baumannii infection alter pro-inflammatory cytokine release leading to severe microbial disease. Our findings provide a better understanding of the impact of these innate immune cells in controlling A. baumannii skin infections.